The Geographic Mobility of Labor and the Rigidity of European Labor Markets - Gabor Kezdi (Hungarian Academy of Sciences, Institute of Economics, 2002)
Regional unemployment and non-participation rates are higher, more disperse, and more stable in Europe than in the U.S. This paper helps understand what may cause this phenomenon. Specifically, it looks at the role of migration in regional differences. I analyze the adjustment mechanisms of regional labor markets in seven countries of continental Europe (Belgium, Germany, Spain, France, Italy, The Netherlands, and Portugal), and the United States. I develop a simple model to understand the role of migration in the adjustment mechanism and estimate comparative static parameters. Under demand shocks, migration elasticities are identified relative to other supply elasticities. I argue that comparative statics give more reliable results than the usual Vector Autoregression approach. I exclude part of the possible supply-induced variation in my analysis. According to the results, aggregate migration elasticities relative to other supply responses are significantly weaker in Europe than in the U.S. The differences are small for the economically most active cohorts, and the aggregate differences are driven primarily by the less active cohorts, both young and old. This suggests that the Europe-US differences in regional inequality are driven at least as much by stronger unemployment and non-participation responses than weaker migration.
Keywords: 330; regional labor markets; migration; labor supply adjustment.